Abstract TP86: Systematic Review Of Aortic Atherosclerotic Plaque In Cryptogenic Stroke - Yu Sakai; Quy Cao; Pouyan Pasyar; Peter B Noel; Jens Witsch; Scott E Kasner; Brett L Cucchiara; Jae W Song (Stroke, 2023)
Introduction: In patients with cryptogenic stroke (CS), complex aortic plaque may be a potential underlying etiology. We performed a systematic review to determine the prevalence of complex aortic plaque in CS patients. Methods: A systematic review and meta-analysis were performed according to PRISMA guidelines (PROSPERO: CRD42022300865). PubMed and EMBASE databases were searched from Jan 1980 to Nov 2021 for studies assessing aortic (ascending, arch, descending) plaque by transesophageal echocardiogram (TEE), CT/CTA, or MRI in at least 10 CS patients. Prevalence rates were pooled using a random-effects model. I 2 statistics assessed heterogeneity. An Egger’s test assessed publication bias. Results: From 2712 articles, 31 met inclusion criteria. Ascending, arch, and descending aorta were assessed in 65%, 100%, 55% of studies, respectively. Studies investigated aortic plaque by TEE (84%), CT/CTA (19%) and MRI (16%). The prevalence of complex aortic plaque in 4666 CS patients was heterogeneous across studies and yielded a summary prevalence of 30% (95% CI 23-38%, I 2 = 96%; Figure 1) contrasting with 11% (95% CI 5-20%, I 2 =83%) in 677 patients without stroke. Prevalence rates in women and men were 26% (95% CI 14%-43%, I 2 = 94%) and 35% (95% CI 21-52%, I 2 = 97%), respectively. To investigate geographic differences, 14 studies from Europe were pooled (32%, 95% CI 23-43%, I 2 =93%), 3 from the Middle East (34%, 95% CI 11-67%, I 2 =94%) and 3 from the US (28%, 95% CI 13-51%, I 2 =90%). No publication bias was detected (p=0.66). Sources of heterogeneity included patient selection, imaging technology (e.g, transducer frequency) and plaque measurement criteria. Conclusions: Studies suggest a prevalence rate of complex aortic plaque in approximately 30% of CS patients. However, significant heterogeneity in the results indicate a need for less variability in CS patient selection and more reproducible imaging methods/criteria for detecting complex aortic plaque.